The development and validation of Indonesian Hope Scale (IHS): A Rasch model analysis - Asiah, Nur; Rusmana, Nandang; Saripah, Ipah; Hamdan, Amirul Hazmi (Universitas Negeri Padang, 2022)
Hope is one of the dimensions of character strength needed in individual personal development. Various instruments continue to be developed to measure a particular hope. The hope scale instrument must be adapted to each culture and country. However, in Indonesia, there has been no research on the development and validation of the hope scale. This study aimed to develop and validate the Indonesian Hope Scale (IHS) using Rasch's model analysis. Participants in this study are 323 students (99 male and 224 female) aged 13-25 years. This study consisted of junior high school students, senior high school students, college students, and postgraduate students. The results showed that Cronbach's Alpha was in the excellent category with a value is 0.82. The item reliability value is 0.99, and the person reliability value is 0.82. The results of Rasch's analysis show that the psychometric characteristics of the 20 items from the Indonesia Hope Scale can meet the requirements and can be used to measure expectations by professionals.